Adopting Tools from Cost and Management Accounting to Improve the Manner in Which Costs in Social Programs are Analyzed and Evaluated - Nadini Persaud (The Evaluation Center at Western Michigan University, 2020)
Background: Managing programs in an environment where financial resources are limited, budget cuts are a reality, and external funding is now fiercely competitive, necessitate that both program administrators and program evaluators have a better understanding of program costs, so that financial resources can be optimized for societal good. This requires serious analysis of cost behavior and a proper understanding of the relationship between a program's variable costs and fixed costs since these costs have implications for clients fees and the number of clients that can be served. These types of analyses are quite routine in the profitability sector, but are considerably underutilized in other sectors. Purpose: This paper will explain how several common strategic management tools from cost and management accounting can be used to present more meaningful and useful cost information, so that social program decision-making and cost-inclusive evaluations can be enhanced. Setting: N/A. Intervention: N/A. Research Design: A desk review was utilized for the discussion of the cost and management accounting concepts and tools outlined in this paper. The paper illustrates how the toolkit of economic evaluation tools can be enhanced by adding tools from cost and management accounting to enhance strategic decision-making. Findings: This paper concludes by noting that program sustainability must be the new name of the game. This necessitates that program administrators and program evaluators start to analyze and evaluate program costs differently. Much work is needed to move towards a different philosophy of thinking with regards to program costs. Program administrators and program evaluators must therefore rise to the challenge and embrace cost analytical methodologies from other disciplines since the use of such methodologies can be beneficial to all concerned.